Gross Anatomical and Morphometrical Investigation on the Scapula of Indian Fox (Vulpes bengalensis (Shaw, 1800)) - Botlagunta, Supriya; Ankem, Prashanth Babu; Vaddi, Karunasri; Sai, Urmila T. (International Journal of Bio-resource and Stress Management, 2025)
The present study was conducted from March, 2023–July, 2024, at the College of Veterinary Science, Proddatur, Andhra Pradesh, India. The scapula bones were collected using the maceration technique to record the gross and morphometrical features. The gross morphological study on the scapula of the Indian fox revealed that it was a triangular bone with two surfaces, three borders, and three angles. The cranial border was thin, convex and showed an anteriorly projected process. The caudal border was thick and straight. The dorsal border was convex. The scapular spine was well developed, increasing in height from above downwards, and it terminated in the acromion process. The maximum length of the right and left scapulae in Indian foxes were 6.0 cm and 5.93 cm respectively. The average maximum width of the right and left scapulae was 3.55 cm. The length of the scapular spine was 5.8 cm. The acromion process consisted of hamate and suprahamate processes. The hamate process was quadrilateral with the blunt end and over-hanged the glenoid notch. The supra-hamate process was triangular and directed caudally. The ratio of supra and infraspinous fossae was approximately 1:1. The subscapular fossa was along the attached border of the spine on the costal surface. The costal surface presented three ridges and the nutrient foramen was observed near the scapular neck. The tuber scapula was not well defined but had a coracoid process towards its costal surface. The glenoid cavity was shallow and oval. The average length and the width of the glenoid cavity were 1.28cm and 0.80 cm respectively.